EVALUASI PELAKSAAN PROGRAM BANTUAN SOSIAL BAGI MASYARAKAT TERDAMPAK DI ERA PANDEMI COVID-19 (Di Desa Kersik Putih Kecamatan Batulicin Kabupaten Tanah Bumbu) - Eva Auliya Putri; Slamet Muchsin; Hayat Hayat (Sekolah Tinggi Pariwisata Mataram, 2021)
Not only in terms of health, the COVID-19 outbreak also has an impact on other sectors, namely social and economic conditions. Currently there are still many people who are experiencing an economic crisis, the problem of poverty is still the center of government efforts to improve the social welfare of the population. Through social assistance programs as a government effort to overcome poverty and unemployment which is increasing. However, there are problems that arise in the implementation of the social assistance program to be precise in Kersik Putih Village, the implementation of Social Assistance is still a dilemma. Many residents still question the recruitment of social assistance recipients, the transparency of the distribution and the Bansos report, and the lack of clarity about the criteria for Bansos recipients and so on. The purpose of this study was to describe an evaluation of the social assistance program implemented in Kersik Putih Village, using the CIPP evaluation indicator with the name formative evaluation proposed by Endang Multiyaningsih.